A Framework for Customized Course Design and Personalized Learning with AI - Aftabi, Elmira; Shirazi, Badrosadat Nategholeslam; Safavi, Ali Akbar; Salimi, Ghasem; Aftabi, Hamidreza (2024 11th International and the 17th National Conference on E-Learning and E-Teaching (ICeLeT), 2024)
The rapid pace of technological advancements and the wide range of subjects present challenges to traditional learning methods. The emergence of artificial intelligence technologies has led to changes and innovations in education, offering a valuable solution that enables the customization of courses to meet individual needs and time constraints. We have proposed a framework for personalized learning aimed at reducing learner confusion amidst an abundance of content and mitigating stress. This framework consists of various steps and provides specific prompts for each learning process, tailored for chatbots. Adaptive steps and prompts help learners create courses tailored to their current educational level, desired achievements, and chosen field of study, ensuring a systematic and personalized learning experience. This paper specifically discusses these approaches using chatbots, such as ChatGPT, with examples including topics like deep learning. Our results demonstrate the method effectively provides personalized access to scientific advancements, encouraging independent and critical thinking, while ensuring proper use of AI tools.